Evaluation of out-patient care educational environment of National Defence University, Malaysia utilizing the ACLEEM Inventory - Haque, Mainul; Othman, Nur Syamirah Aishah; Lutfi, Siti Nur Najihah; Islam, Md Zakirul; A. Rahman, Nor Azlina; Kibria, Golam Mohammad; Haque, Emdadul; Majumder, Md Anwarul Azim; Gnanou, Justin V (AYT Bilimsel Araştırmalar, 2018)
Purpose: A friendly educational environment is required for optimal learning, and students should be asked to provide feedback on their experiences to improve curriculum. Moreover, students’ academic progress, mental growth, and physical well-being are influenced by the educational and clinical environment of the institute. Essential constituents of the educational climate include atmosphere, number of proper teaching-learning sessions and available amenities. Primary health care and ambulatory settings allow students ample opportunities to interact with patients and observe health promotional activities more often practiced at the community levels. The study aims to evaluate the outpatient care educational environment of National Defense University of Malaysia by seeking feedback from medical students using Ambulatory Care Educational Environment Measure (ACLEEM) instrument. Methods: This was a cross-sectional study. The study participants were medical students of the earlier mentioned university. The universal sampling method was adopted. The ACLEEM validated instrument was utilized for the data collection. The instrument was developed on the basis of 5-point Likert Scale (Minimum: 0, and Maximum: 4). Results: The response rate 100%. Most respondents were male, Malay and Muslim. The total mean score was 1.0±0.4. The domain mean scores for clinical teaching, clinical training, and support were 0.8±0.4, 1.1±0.4, and 1.1±0.5, respectively. Conclusions: The ACLEEM questionnaire was found to be valid and reliable for local UPNM, Malaysian context. However, the overall ACLEEM scores reported for the present study is low, and some areas that could be improved. The UPNM authority should take appropriate measures to improve the educational environment to enhance the academic experiences of the medical students.